Influence of Pre- and Intraoperative Local Anaesthetic in Strabismus Surgery under General Anaesthesia in Adults - Felber, Daniel; Roulez, Francoise; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2024)
Background As studies have shown a reduction in the occurrence of the oculocardiac reflex with the addition of local anaesthesia, we changed our care regime accordingly a few years ago. To promote and establish better patient care, we retrospectively analysed the files of our patients who underwent strabismus surgery from 2013 to 2021 in order to compare strabismus surgery under general anaesthesia with and without local anaesthetics in a routine clinical setting.Patients and Methods Data from 238 adult patients who had undergone strabismus surgery could be extracted from the files: G1: n = 102, only general anaesthesia; G2: n = 136, preoperative application of tetracaine eye drops and intraoperative subtenon lidocaine/levobupivacaine in addition to general anaesthesia. We compared the two groups in regard to the frequency of oculocardiac reflex, the amount of atropine needed to treat, as well as the amount of antiemetic and analgesic medication given, and time spent in the recovery room.Results Mean age of G1 was 50 years and 52 years in G2. There was no significant difference between the kind of surgeries (recessions/resections), the number of patients who had undergone a reoperation, or the duration of the operations. Adding local anaesthetics resulted in significantly less occurrence of oculocardiac reflex (p = 0.009), a reduction in the need for atropine, analgesic, or antiemetic medication, as well as reduced time in the recovery room.Conclusion As this increases patient safety and comfort and is cost-effective (less time in the recovery room), we recommend adding perioperative local anaesthesia to strabismus surgery performed under general anaesthesia.
Keywords: strabismus surgery; atropine; perioperative; oculocardiac reflex; local anaesthesia